Ion fluxes through KCa2 (SK) and Cav1 (L-type) channels contribute to chronoselectivity of adenosine A1 receptor-mediated actions in spontaneously beating rat atria - Paulo eCorreia- (Frontiers Media S.A., 2016)
Impulse generation in supraventricular tissue is inhibited by adenosine and acetylcholine via the activation of A1 and M2 receptors coupled to inwardly rectifying GIRK/KIR3.1/3.4 channels, respectively. Unlike M2 receptors, bradycardia produced by A1 receptors activation predominates over negative inotropy. Such difference suggests that other ion currents may contribute to adenosine chronoselectivity. In isolated spontaneously beating rat atria, blockade of KCa2/SK channels with apamin and Cav1 (L-type) channels with nifedipine or verapamil, sensitized atria to the negative inotropic action of the A1 agonist, R-PIA, without affecting the nucleoside negative chronotropy. Patch-clamp experiments in the whole-cell configuration mode demonstrate that adenosine, via A1 receptors, activates the inwardly-rectifying GIRK/KIR3.1/KIR3.4 current resulting in hyperpolarization of atrial cardiomyocytes, which may slow down heart rate. Conversely, the nucleoside inactivates a small conductance Ca2+-activated KCa2/SK outward current, which eventually reduces the repolarizing force and thereby prolong action potentials duration Ca2+ influx into cardiomyocytes. Immunolocalization studies showed that differences in A1 receptors distribution between the sinoatrial node and surrounding cardiomyocytes do not afford a rationale for adenosine chronoselectivity. Immunolabelling of KIR3.1, KCa2.2, KCa2.3 and Cav1 was also observed throughout the right atrium. Functional data indicate that while both A1 and M2 receptors favor the opening of GIRK/KIR3.1/3.4 channels modulating atrial chronotropy, A1 receptors may additionally restrain KCa2/SK activation thereby compensating atrial inotropic depression by increasing the time available for Ca2+ influx through Cav1 (L-type) channels.